Transient Palsy of Recurrent Laryngeal Nerve Postresection of Giant Substernal Goiter - Muhoozi, Rwakaryebe; Yu, Fenglei; Tang, Jingqun; Wang, Xiang (The Thoracic and Cardiovascular Surgeon Reports, 2014)
We report a case of a female patient aged 46 years with a history of nodular goiter for which she had a subtotal thyroidectomy 31 years ago. She was referred to the emergency department of our hospital because of dyspnea and chest pain for 20 days, then developed cyanosis and edema of the head and upper extremities. Chest X-ray revealed tracheal repulsion. Cervical and thoracic computed tomography showed a giant solid and a cystic mass in the anterior mediastinum and bilateral pleural effusion. The neck ultrasound did not show any thyroid masses. An exploratory thoracotomy with extensive resection considering the anatomical relation of the mass and the adjacent structures was planned. Immediately after the operation, the patient developed airway complications that resolved in 7 days. The tumor was confirmed pathologically as nodular goiter. The overall outcome of the patient was positive; she is healthy after more than 12 months of follow-up. This report examines the approach to diagnosis and management of one of the most common surgical complication associated with substernal goiters.
Keywords: mediastinum; recurrent laryngeal nerve; substernal goiter